2022
DOI: 10.2196/28095
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Home Stay and Symptom Severity in Major Depressive Disorder: Preliminary Findings From a Multicenter Observational Study Using Geolocation Data From Smartphones

Abstract: Background Most smartphones and wearables are currently equipped with location sensing (using GPS and mobile network information), which enables continuous location tracking of their users. Several studies have reported that various mobility metrics, as well as home stay, that is, the amount of time an individual spends at home in a day, are associated with symptom severity in people with major depressive disorder (MDD). Owing to the use of small and homogeneous cohorts of participants, it is uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…While six articles examined overall mental health [ 13 , 24 , 25 , 26 , 27 , 68 ], other studies examined specific factors such as mood [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and stress [ 76 , 77 , 78 ]. Additionally, studies also examined specific mental health conditions such as depression [ 7 , 8 , 67 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], schizophrenia [ 90 , 91 , 92 , 93 ], and bipolar disorder [ 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While six articles examined overall mental health [ 13 , 24 , 25 , 26 , 27 , 68 ], other studies examined specific factors such as mood [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and stress [ 76 , 77 , 78 ]. Additionally, studies also examined specific mental health conditions such as depression [ 7 , 8 , 67 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], schizophrenia [ 90 , 91 , 92 , 93 ], and bipolar disorder [ 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another example, Ref. [ 7 ] collected location data to determine if there was a correlation between time spent at home and self-reported depressive symptoms. Identifying feature correlations and using machine learning to predict behavior: These types of studies (22 studies) not only identified correlation between smartphone-sensed features, but also built machine-learning models to evaluate if these were able to predict user behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We utilized a 'bootstrap-like' statistical testing paradigm that creates multiple models via a participant independent random sampling of the windowed eGeMAPS features. Using this paradigm, we applied a two-steps methodology in our analysis to identify features re ective of schizotypy, depression and generalized anxiety symptoms (Laiou et al, 2022).…”
Section: Statistical Analysesmentioning
confidence: 99%